(untitled) (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
This article presents the implications of Abdullah and Khalifatullah’s concepts in character education. The concept of Abdullah emphasizes awareness as a servant of God in shaping the character of learners, while the concept of Khalifatullah underlines the responsibility of man as a substitute for Allah. The implications of these two concepts include the development of good morals, social and moral awareness, spiritual intelligence, and just leadership. By understanding the implications of the concepts of Abdullah and Khalifatullah, character education can produce individuals who are aware of the vertical relationship with God, have noble morals, are socially responsible, and have high environmental awareness. This effort can form a quality generation and contribute positively to society. Character education that integrates the concepts of Abdullah and Khalifatullah requires a holistic approach involving academic, moral, spiritual, and social aspects. The purpose of Islamic education based on this concept is to form a generation that is faithful, has noble character, is socially responsible, and ready to become a just leader.